Role of diacylglycerol O-acyltransferase 1 (DGAT1) in lipolysis and autophagy of adipose tissue from ketotic dairy cows - Xu, Qiushi; Fan, Yunhui; Mauck, John; Loor, Juan J.; Sun, Xudong; Jia, Hongdou; Li, Xinwei; Xu, Chuang (Journal of dairy science, 2024)
The list of standard abbreviations for JDS is available at adsa.org/jds-abbreviations-24. Nonstandard abbreviations are available in the Notes. High-yielding dairy cows in early lactation often encounter difficulties in meeting the energy requirements essential for maintaining milk production. This is primarily attributed to insufficient dry matter intake, which consequently leads to sustained lipolysis of adipose tissue. Fatty acids released by lipolysis can disrupt metabolic homeostasis. Autophagy, an adaptive response to intracellular environmental changes, is considered a crucial mechanism for regulating lipid metabolism and maintaining a proper cellular energy status. Despite its close relationship with aberrant lipid metabolism and cytolipotoxicity in animal models of metabolic disorders, the precise function of diacylglycerol o-acyltransferase 1 (DGAT1) in bovine adipose tissue during periods of negative energy balance is not fully understood, particularly regarding its involvement in lipolysis and autophagy. The objective of the present study was to assess the effect of DGAT1 on both lipolysis and autophagy in bovine adipose tissue and isolated adipocytes. Adipose tissue and blood samples were collected from cows diagnosed as clinically ketotic (n = 15) or healthy (n = 15) following a veterinary evaluation based on clinical symptoms and serum concentrations of BHB, which were 3.19 mM (interquartile range = 0.20) and 0.50 mM (interquartile range = 0.06), respectively. Protein abundance of DGAT1 and phosphorylation levels of unc-51-like kinase 1 (ULK1), were greater in adipose tissue from cows with ketosis, whereas phosphorylation levels of phosphoinositide 3-kinase (PI3K), protein kinase B (AKT), and mammalian target of rapamycin (mTOR) were lower. Furthermore, when adipocytes isolated from the harvested adipose tissue of 15 healthy cows were transfected with DGAT1 overexpression adenovirus or DGAT1 small interfering RNA followed by exposure to epinephrine (EPI), it led to greater ratios and protein abundance of phosphorylated hormone-sensitive triglyceride lipase (LIPE) to total LIPE and adipose triglyceride lipase (ATGL), while inhibiting the protein phosphorylation levels of ULK1, PI3K, AKT, and mTOR. Overexpression of DGAT1 in EPI-treated adipocytes reduced lipolysis and autophagy, whereas silencing DGAT1 further exacerbated EPI-induced lipolysis and autophagy. Taken together, these findings indicate that upregulation of DGAT1 may function as an adaptive response to suppress adipocytes lipolysis, highlighting the significance of maintaining metabolic homeostasis in dairy cows during periods of negative energy balance.